2022
DOI: 10.3390/jpm12101684
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling in Non-Squamous Non-Small Cell Lung Carcinoma: Towards a Switch to Next-Generation Sequencing Reflex Testing

Abstract: Molecular diagnosis of lung cancer is a constantly evolving field thanks to major advances in precision oncology. The wide range of actionable molecular alterations in non-squamous non-small cell lung carcinoma (NS-NSCLC) and the multiplicity of mechanisms of resistance to treatment resulted in the need for repeated testing to establish an accurate molecular diagnosis, as well as to track disease evolution over time. While assessing the increasing complexity of the molecular composition of tumors at baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…In conclusion, the present study demonstrated that performing IHC to evaluate the ROS1 rearrangement status in advanced NS-NSCLC should be abandoned nowadays in favor of ultrafast RNA NGS reflex testing [ 16 , 17 , 43 ]. ROS1 FISH is still useful for validation of the diagnosis in the case of uncertain NGS results and/or of very small tissue biopsies with a few tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the present study demonstrated that performing IHC to evaluate the ROS1 rearrangement status in advanced NS-NSCLC should be abandoned nowadays in favor of ultrafast RNA NGS reflex testing [ 16 , 17 , 43 ]. ROS1 FISH is still useful for validation of the diagnosis in the case of uncertain NGS results and/or of very small tissue biopsies with a few tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the developments in digital pathology may encounter several problems, depending on the institution and laboratories, notably with respect to different interfaces of information systems, the software and the work of the laboratory technicians and the pathologist. An increase in the automation of procedures including nucleic acid extraction (from tissue or liquids), quality control, the preparation of libraries and sequencing, and bioinformatic tools should allow in-house adoption of more and more complex genomic analyses [ 80 ]. The pathologist must be one of the essential players in therapeutic decision making in multidisciplinary boards [ 11 ].…”
Section: Challenges Faced By the Thoracic Pathologist And Suggestions...mentioning
confidence: 99%
“…However, the regular participation at molecular boards is time consuming and requires the pathologist to reorganize the workload. Another challenge concerns the setup of reflex NGS, without waiting for the request from the clinician, in particular for advanced staged tumors [ 80 ]. Managing the impact on laboratory staff and costs also needs to be addressed, as well as the storage, analysis, and application of complex data, including also data protection [ 80 , 81 ].…”
Section: Challenges Faced By the Thoracic Pathologist And Suggestions...mentioning
confidence: 99%
“…3,4 Compared with other sequencing modalities, NGS holds many advantages, for instance, high throughput to fully sequence all types of mutations for many genes (hundreds to thousands), the sensitivity and the speed. 1,2,5 Moreover, testing in a single assay is both timely and costeffective as it can detect all four main classes of genomic alterations: base substitutions insert and deletions, copy number alterations, and rearrangements or fusions. 1,2,6,7 NGS has identified novel genetic alterations contributing to oncogenesis, cancer progression, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation sequencing (NGS) is a high complex molecular technique that makes it possible to simultaneously test for a very large panel of genes by allowing parallel sequencing of numerous small nucleic acid fragments 3,4 . Compared with other sequencing modalities, NGS holds many advantages, for instance, high throughput to fully sequence all types of mutations for many genes (hundreds to thousands), the sensitivity and the speed 1,2,5 . Moreover, testing in a single assay is both timely and cost‐effective as it can detect all four main classes of genomic alterations: base substitutions insert and deletions, copy number alterations, and rearrangements or fusions 1,2,6,7 …”
Section: Introductionmentioning
confidence: 99%